Do investing in information technology and intellectual capital improve firm value in the financial technology era? - Ariny Maghfiroh; Erwin Saraswati; Endang Mardiati (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This research aims to prove the impact of information technology investments and intellectual capital on firm value (Tobin’s Q) in the financial technology era.Design/Methodology/Approach: This study’s population was banks listed on the Indonesian Stock Exchange (ISE) during 2017–2022. Purposive sampling was utilized to choose a sample of 46 banks, resulting in a total of 112 observations during six years. This research employed GMM regression for empirical analysis, considering endogeneity. Research findings: The study revealed that while investments in information technology exerted a favorable influence on firm value, intellectual capital had a beneficial impact on firm value. Human Capital Efficiency (HCE) and Capital Employed Efficiency (CEE) positively impacted firm value. However, the variables Structural Capital Efficiency (SCE) and Relational Capital Efficiency (RCE) did not have any effect on firm value. The variables being controlled for in this study comprised corporate level, industry level, and banking type. The financial success of a corporation could be influenced by the corporate level, determined by the organization's size. The influence of industrial level and bank type on company firm value was limited due to the dynamic nature of market conditions and the intensifying competition within the banking system.Theoretical contribution/ Originality: This research contributes theoretically to the field of signaling theory by presenting an advantageous analytical framework to examine the effects of IT investments in the dynamic financial sector.Practitioner/Policy implication: This research contributes to investors in determining investment decisions and the council of commissioners to enhance supervision of IT investments, encourage banking to innovate in leveraging information technology, and introduce new products that can meet customer needs.Research limitation/Implication: The research focuses exclusively on banks listed on ISE and exclusively employs the MVAIC methodology for research purposes. Since this research was limited to the financial statements presented by the company, so some necessary data were not available, requiring an interview or spreading the questionnaire to the sample used. This research was also limited to banking in Indonesia, so the samples used were also limited, and there needs to be a comparison.